2016
DOI: 10.3390/ijms17060950
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Latest Advances in Encrypted Bioactive Peptides from Protein-Rich Waste

Abstract: Bioactive peptides are considered the new generation of biologically active regulators that not only prevent the mechanism of oxidation and microbial degradation in foods but also enhanced the treatment of various diseases and disorders, thus increasing quality of life. This review article emphasizes recent advances in bioactive peptide technology, such as: (i) new strategies for transforming bioactive peptides from residual waste into added-value products; (ii) nanotechnology for the encapsulation, protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(95 citation statements)
references
References 154 publications
0
78
0
5
Order By: Relevance
“…The ultrafiltration system using 1–10 kDa MWCO membranes is usually applied to separate bioactive peptides into fractions with different molecular weights [37,38]. This is because the size of ACE-inhibitory peptides is generally between 2 and 30 amino acids [39].…”
Section: Resultsmentioning
confidence: 99%
“…The ultrafiltration system using 1–10 kDa MWCO membranes is usually applied to separate bioactive peptides into fractions with different molecular weights [37,38]. This is because the size of ACE-inhibitory peptides is generally between 2 and 30 amino acids [39].…”
Section: Resultsmentioning
confidence: 99%
“…Citrus fruits are processed, not only to obtain juice, but also, in the canning industry to produce jam and segments of mandarin. Lemes et al (2016) reported bioactive peptides as the new generation of biologically active regulators that can prevent oxidation and microbial degradation in foods, and might be helpful in treatment of various diseases. These can be extracted from residual waste and incorporated into value added products.…”
Section: Food Waste As a Source Of Bioactive Compoundsmentioning
confidence: 99%
“…As discussed, the main component of meat co-products, on a dry basis, is protein; thus, these 206 by-products are a potential source of bioactive peptides which can be extracted, purified and 207 commercialised as a very high-added value product (Lemes et al, 2016 preventing heart disease (Williams, 2007) hence exudate and cook-out may be good sources.…”
mentioning
confidence: 99%